Human Seasonal Influenza Viruses in Swine Workers in Lagos, Nigeria: Consequences for Animal and Public Health - Abdul-Azeez A. Anjorin; Aurélie Sausy; Claude P. Muller; Judith M. Hübschen; Sunday A. Omilabu; Chantal J. Snoeck (Viruses, 2023)
The influenza A virus has been scarcely investigated in pigs in Africa, with rare detection prior to 2009. The spread of A(H1N1)pdm09 changed the epidemiology due to frequent human-to-swine transmission and the emergence of various new reassortants. This study therefore aimed at estimating the level of circulation and characterizing influenza A viruses at the interface between swine workers, who are crucial players in the inter-species transmission of influenza A viruses, and their animals in several farms in Nigeria, a hub for pig production in Africa. This cross-sectional study showed that 24.6% (58/236) of the pig serum samples collected in 2013–2014 had anti-influenza A antibodies in the absence of vaccination programs, but none of the pig swabs (n = 1193) were positive according to RT-qPCR. Viral RNA was detected in 0.9% (2/229) of swine workers sampled at their place of work, and the strains were characterized as A(H1N1)pdm09 and seasonal A(H3N2). Our results highlight that more awareness of swine workers regarding the consequences of reverse zoonosis for animal and public health is warranted. Annual vaccination and the wearing of masks when experiencing influenza-like symptoms would help decrease influenza inter-species transmission, while surveillance should be adequately supported for early detection.